Pengaruh Prenatal Yoga Terhadap Kecemasan Pada Ibu Hamil Trimester Iii Di Wilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu Tahun 2025 - Ena Purnama Putri; Ronalen Br. Situmorang; Danur Azissah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
According to WHO, 287,000 women die due to complications of pregnancy and childbirth. The aim is to determine the frequency distribution before doing prenatal yoga movements in pregnant women in the third trimester, to determine the frequency distribution after doing prenatal yoga movements in pregnant women in the third trimester and to determine the effect before and after doing prenatal yoga movements in pregnant women in the third trimester. This study is a quantitative study with a pre-experimental design using a one-group pretest–posttest design. In this design, measurements are carried out twice, namely before being given treatment (pretest) and after being given treatment (posttest) prenatal yoga on the same group of subjects, so that changes can be known before and after the intervention. The results showed that before doing prenatal yoga movements, most respondents (60.0%) experienced moderate anxiety and almost half of respondents (40.0%) experienced severe anxiety. After doing prenatal yoga movements, most respondents (70.0%) experienced mild anxiety, almost half of respondents (40.0%) experienced moderate anxiety and a small portion of respondents (20.0%) experienced severe anxiety. With the results of the normality test ρ = 0.000 (ρ